1975
DOI: 10.1038/bjc.1975.88
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal polyps in American negroes and Nigerian africans

Abstract: Summary.-Forty Africans from Nigeria and 89 American negroes with colorectal polyps were analysed by age, sex and type of polyp. The Nigerians were much the younger group (mostly under 20 years of age, whereas most of the American negroes were over 50) and 'far fewer of their polyps were truly neoplastic (7.5% compared with 87% of the Americans). These differences may be partly due to the American negro population being older than the Nigerian, and partly to environmental factors like those previously postulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Most of the polyps were detected in male patients younger than 50 years. An old study had shown that compared with Negro Americans, Nigerians were likely to be younger and have fewer neoplastic polyps [28]. Although the incidence of colorectal cancer may be rising in Nigeria, there is little doubt that colorectal cancer incidence is lower in West Africa compared to the West [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the polyps were detected in male patients younger than 50 years. An old study had shown that compared with Negro Americans, Nigerians were likely to be younger and have fewer neoplastic polyps [28]. Although the incidence of colorectal cancer may be rising in Nigeria, there is little doubt that colorectal cancer incidence is lower in West Africa compared to the West [29].…”
Section: Discussionmentioning
confidence: 99%
“…1996). However, some studies have looked at the occurrence of polyps in Nigerians: Williams et al . (1975), Williams and Prince (1975) studied surgical biopsies of polyps from 40 Nigerians in Ibadan over a period of 10 years and found an average age of 13 years with juvenile polyps as the most common histopathologic type.…”
Section: Discussionmentioning
confidence: 99%
“…Observations on intercountry variation and migrant populations have indicated that race per se does not play a determinant role in polyp prevalence or incidence of colon cancer. Migrants from lowrisk to high-risk countries acquire the high prevalence of polyps and the high incidence of cancers of the host countries as has been proved for Caucasian, Japanese and Negro migrants (Staszewski et al, 1965;Haenszel et al, 1968;Williams et al, 1975;and Correa et al, 1977). The negroes of Brazil apparently have acquired an intermediate risk for adenomatous polyps when compared with the African negroes (Bremmer et al, 1970;Williams et al, 1975).…”
Section: Discussionmentioning
confidence: 90%
“…Migrants from lowrisk to high-risk countries acquire the high prevalence of polyps and the high incidence of cancers of the host countries as has been proved for Caucasian, Japanese and Negro migrants (Staszewski et al, 1965;Haenszel et al, 1968;Williams et al, 1975;and Correa et al, 1977). The negroes of Brazil apparently have acquired an intermediate risk for adenomatous polyps when compared with the African negroes (Bremmer et al, 1970;Williams et al, 1975). While in our opinion the Siio Paul0 results provide additional support for the proposition that race is not an important determinant, some aspects of the local comparisons warrant comment.…”
Section: Discussionmentioning
confidence: 90%